Screen‐printed Electrodes for the Determination of Iridium in Drugs. Issue 12 (16th October 2018) - Zaguirre, Marc; Ariño, Cristina; Serrano, Núria; Díaz‐Cruz, José Manuel; Esteban, Miquel
Abstract: Among the impurities that must be controlled in drugs and pharmaceuticals, metal ions are considered. These metal impurities appear in those products because of their use as catalysts. Although Pharmacopeias recommend ICP based methods for their determination, the use of electroanalytical techniques can be considered as a sensible, selective and non‐expensive alternative for the determination of heavy metal ions in general and metal impurities in particular. In the present work, we propose a differential pulse voltammetric method based on the use of carbon based‐screen‐printed electrodes (graphite, nanotubes or nanofibers) that allows the determination of iridium in drugs at the concentration limits recommended by official organisms. Carbon screen‐printed electrode modified with nanotubes (CNT‐SPCE) is the sensor that provided the best LOD and LOQ (0.03 and 0.10 mg L −1 respectively). Then, the proposed method was applied to the voltammetric determination of iridium in spiked drug samples purchased in local chemists using CNT‐SPCE. Abstract :